The Effectiveness of Puzzle Game-Based Learning Media in Improving Mathematics Science Problem Solving Skills - Hidayatulloh; Noerhasmalina (Jurnal Penelitian Pendidikan IPA, 2025)
Problem solving ability is an important skill in learning mathematics, especially in geometry material that requires conceptual understanding and spatial analysis. This study aims to test the effectiveness of puzzle games in improving mathematical science problem solving abilities. The method used in this study was a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 60 grade XII students who were divided into two groups, an experimental group using ethnomathematics puzzle games and a control group using conventional methods. Data were obtained through problem solving tests before and after treatment, then analyzed using N-gain and t-test with SPSS to determine the significance of differences in learning outcomes between the two groups. The results showed that the experimental group experienced a significant increase compared to the control group (p <0.001). The average N-gain value in the experimental group was 0.70 in the high category, while in the control group it was 0.46 in the moderate category. In addition, the effect size analysis of 1.39 showed that the use of ethnomathematics puzzle games had a major impact on improving students' mathematical science problem solving abilities. Puzzle games are an effective learning medium in improving students' mathematical science problem-solving abilities in geometry material. In addition, this approach can enrich students' learning experiences by connecting mathematical concepts with relevant cultural contexts. Therefore, the use of ethnomathematics puzzle games is recommended as an innovative learning strategy that can be applied in teaching mathematics at MAN 1 Tanggamus.